Legal provision for the rights of persons who receive rehabilitation assistance (Bulletin of Kharkiv National University of Internal Affairs, 2024)
The research is devoted to the problems of legal provision of the rights of persons who receive rehabilitation assistance. The author examines the norms of international and national legislation that enshrine the rights of citizens in the field of healthcare. The works of scholars who have examined the peculiarities of exercising certain patients’ rights are studied.The article describes the legislative acts regulating the rights of a patient in a rehabilitation institution in Ukraine. It is indicated that certain patient rights are enshrined in the Civil Code of Ukraine and the Fundamentals of Healthcare Legislation. Special rights of the patients of rehabilitation institutions are provided for by the Laws of Ukraine “On Rehabilitation in the Healthcare Sector” and “On Rehabilitation of Persons with Disabilities in Ukraine”.The classification of patient's rights into socio-economic, legal, informational, ethical and those related to ensuring the quality of rehabilitation care is proposed. It is indicated that informational rights include the right to information about rights and obligations, diagnosis, functional limitations, nature of treatment, and preservation of medical confidentiality. It is concluded that socio-economic rights consist in the possibility of access to free rehabilitation services at the expense of budgetary funds under the programme of State medical guarantees. It is noted that ethical rights provide for a humane and respectful attitude of medical personnel towards patients. Among the legal rights of the patient is the possibility of judicial and administrative protection of the patient’s rights by applying to law enforcement agencies and courts. The patient has the right to qualified rehabilitation care.Proposals for amendments to the current legislation are made. The necessity to systematise patient rights and provide for them in a separate Law of Ukraine “On Protection of Patients’ Rights” is emphasised.